Whole-body alternating magnetic field exposure decreased urinary adrenaline and noradrenaline levels in humans due to non-thermal effect of the magnetism - NAKAZATO, Seiki; SETO, Akira; YAMAMOTO, Tatsutaka; KUSAKA, Chikaaki; HISAMITSU, Tadashi (Nihon Haipāsāmia Gakkai shi, 1997)
Non-thermal effects of magnetic field and electromagnetic field on the living body have been studied using alternating magnetic field (AMF) generation device of 50Hz, 0.08T (800gauss). This device has hardly heating ability used for hyperthermia. In this study, we developed a special use chair for the whole-body AMF exposure. This chair was provided 11 AMF generation devices. The actual intensity of the AMF exposure chair to which the human body was exposed was 0.3 to 7 mT (3 to 70 gauss). Using the AMF exposure chair, a whole-body AMF stimulation was applied to 8 male subjects for 30 minutes, and the urinary levels of adrenaline (Ad), noradrenaline (NA) and VMA (Ad and NA's final metabolite) were measured. Furthermore, the blood flow of the right shoulder and the right third finger tip, and the armpit temperature were also measured. In the control group of non AMF exposure (n=7), there was not significant difference between pre-experiment and post-one in any clinical test item. Contrary to this, in comparison to the pre-experimental levels as 100%, the AMF exposure group (n=8) decreased Ad down to 51.1% (p < 0.01), NA 57.0% (p < 0.05), VMA 60.9% (p < 0.05), and increased the right shoulder blood flow up to 226.3% (p < 0.01) and the blood flow of the right third finger tip 174.9% (p < 0.001). However, the armpit temperature was no change in even AMF exposed group. From above, it is concluded that these phenomena are thought to be a non-thermal effect of the AMF, and are suggested that the whole-body AMF exposure reduce the synthesis or the release of Ad and NA. In the future, this non-thermal effect of AMF would be beneficial to hyperthermic therapy.